Determine the product (x^1/3 + y^1/3)(x^2/3 - x^1/3 y^1/3 + y^2/3) without using long multiplication.
1 Answer | Add Yours
The product `(x^(1/3) + y^(1/3))(x^(2/3) - x^(1/3)*y^(1/3) + y^(2/3))` has to be determined without using conventional multiplication.
If `x^(1/3)` = a and `y^(1/3)` = b, the given expression is:
(a + b)(a^2 - ab + b^2)
=> a^3 + b^3
=> x + y
The product `(x^(1/3) + y^(1/3))(x^(2/3) - x^(1/3)*y^(1/3) + y^(2/3)) = x + y`
Join to answer this question
Join a community of thousands of dedicated teachers and students.Join eNotes